Design and analysis of convergence and stability of iterative methods for solving nonlinear equations: Diseño y análisis de la convergencia y estabilidad de métodos iterativos para la resolución de ecuaciones no lineales - Solís Zúñiga, Armando Gabriel (2021)
One stream in numerical analysis is the creation of new iterative methods for the resolution of non-linear equations; optimal processes are sought in contrast with their order of convergence and the number of functional evaluations compared to usual known methods. This article shows a design of a new parametric family of iterative methods based on the Chun's family of methods which contains the particular case of the Ostrowski's scheme. Through an analysis with complex dynamic it is intended to visualize dynamic planes and parameters' planes to choose the best parameter who brings more stable behavior for the scheme under study and make it more efficient.